Phosphated cyclodextrins as water-soluble chiral NMR solvating agents for cationic compounds - Puentes, Cira Mollings; Wenzel, Thomas J. (Beilstein Journal of Organic Chemistry, 2017)
The utility of phosphated α-, β- and γ-cyclodextrins as water-soluble chiral NMR solvating agents for cationic substrates is described. Two sets of phosphated cyclodextrins, one with degrees of substitution in the 2–6 range, the other with degrees of substitution in the 6–10 range, are examined. Results with 33 water-soluble cationic substrates are reported. We also explored the possibility that the addition of paramagnetic lanthanide ions such as praseodymium(III) and ytterbium(III) further enhances the enantiomeric differentiation in the NMR spectra. The chiral differentiation with the phosphated cyclodextrins is compared to prior results obtained with anionic carboxymethylated cyclodextrins. There are a number of examples where a larger differentiation is observed with the phosphated cyclodextrins.
Keywords: chiral; chiral differentiation; cyclodextrin; enantiomer; enantiomeric purity; NMR